THE EFFECT OF RECYCLING TRAPS AND UPWELLING ON ESTUARINE CHEMICAL FLUX ESTIMATES - Shiller A.M. (My University, 1996)
Property-salinity plots are commonly used in the interpretation of estuarine and coastal dissolved chemical distributions as well as in making estimates of fluxes to the open ocean. Previous work has explored the interpretation of these diagrams from a theoretical point of view and has pointed out some of the assumptions inherent in their use. In this report a simple box model is used to explore the effect of recycling traps and upwelling on property-salinity plots. It is shown that both of these phenomena, if not accounted for, can lead to erroneous conclusions about dissolved fluxes to the open ocean. Simple relationships are derived from the box model which can be used to evaluate the effects of recycling and upwelling. The model is applied to the Amazon outflow region where recycling is important and to waters outside San Francisco Bay where upwelling is important. Additional analysis of the Louisiana Shelf and the western North Atlantic indicates the need for further consideration of upwelling effects in these regions.